Jalan Yang Kalsom musical entertains theatre-goers - Noor Afiza, Mohd Asmi (2019)
Universiti Malaysia Pahang (UMP), in collaboration with the state’s Department of Broadcasting, Radio Televisyen Malaysia (RTM) Pahang, recently presented a solid musical performance on “Jalan Yang Kalsom: Sebuah Muzikal” (JYKSM) on April 14, 2019 – which revolves around the lives of multi-racial residents at Jalan Yang Kalsom in Ipoh, Perak, circa 1970s.